GURU NANAK DEV: THE TORCHBEARER OF RELIGIOUS AWAKENING - Narinderkaur (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In the beginning of the 16th century, when Guru Nanak lived and preached his message of love and equality, Punjab was part and parcel of the Delhi sultanate which was ruled by Sultan SikandarLodhi. Politically, it was an oppressive and unjust regime, marked by exploitation and injustice. Socially, it was a divided house wherein a large part of humanity was denied even the fundamental rights. Non-Muslims were made to live like second class citizens. The ruling class had lost all sense of justice and the order of the day. The moral and spiritual degeneration was also keeping pace only too well with the political disruption from which the country had been suffering.